Analysis of Student Learning Styles Using Fleming's VARK Model in Science Subject - Subagja, Sigit; Rubini, Bibin (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
The implementation of high-quality learning is something teachers must ensure. Consequently, teachers need to be able to design engaging learning procedures that draw students' attention to the subjects they are teaching. Understanding a student's preferred learning style is one of the necessary teachers. People with learning styles closely tied to their environments and personalities are adjusted. The process of receiving knowledge will be improved by defining the learning material to the learner's preferred learning style. One of the most used diagnostic tools for determining learning type is the VARK model. The visual, Auditory, Read/Write, and kinesthetic learning styles are divided into four divisions in the VARK paradigm. This research aims to identify the dominant learning style among science students. A qualitative descriptive methodology used one hundred junior high school students as research participants. Diagnostic exams and interviews were the tools used. Data analysis was carried out qualitatively by reducing data, presenting data, and making conclusions. According to the findings, 35% of students are kinesthetic learners, with 30% being visual, 21% being Auditory, and 14%t being Read/Write. Identifying learning tools, such as choosing learning models, creating and choosing materials, and learning media and assessment approaches that are more effective in accordance with student learning styles, can be done by developing one's understanding of learning styles.